2014
DOI: 10.1103/physrevlett.112.220501
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Realization of a Compressed Quantum Simulation of a 32-Spin Ising Chain

Abstract: Certain n-qubit quantum systems can be faithfully simulated by quantum circuits with only O(log(n)) qubits [B. Kraus, Phys. Rev. Lett. 107, 250503 (2011)]. Here we report an experimental realization of this compressed quantum simulation on a one-dimensional Ising chain. By utilizing an nuclear magnetic resonance quantum simulator with only five qubits, the property of ground-state magnetization of an open-boundary 32-spin Ising model is experimentally simulated, prefacing the expected quantum phase transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…Now we turn to the experimental implementation of the quantum algorithm for OCR. The widely utilized nuclear magnetic resonance (NMR) technique [20][21][22][23][24] is employed to realize the four-qubit quantum processor. The experi ments are carried out on a Bruker AV-400 spectrometer at 306 K. The sample used is the l3C-iodotrifluroethylene (C2F3I) dissolved in t/-chloroform, which consists of a 13C nuclear spin and three 19F nuclear spins.…”
Section: )mentioning
confidence: 99%
“…Now we turn to the experimental implementation of the quantum algorithm for OCR. The widely utilized nuclear magnetic resonance (NMR) technique [20][21][22][23][24] is employed to realize the four-qubit quantum processor. The experi ments are carried out on a Bruker AV-400 spectrometer at 306 K. The sample used is the l3C-iodotrifluroethylene (C2F3I) dissolved in t/-chloroform, which consists of a 13C nuclear spin and three 19F nuclear spins.…”
Section: )mentioning
confidence: 99%
“…Said differently, the KZM can be extended to account for the full distribution of topological defects.The quantum Ising model in a transverse field.-As a paradigmatic model of a quantum phase transition we consider the one dimensional quantum Ising model [25,26]. The Hamiltonian of a chain of N spins in a transverse magnetic field g reads,Its experimental study is amenable via quantum simulation that has been reported in a variety of platforms including trapped ions, [27,28], superconducting circuits [29,30], Rydberg gases [31], and NMR experiments [32]. We consider periodic boundary conditions σ N+1 = σ 1 with even N, for simplicity.…”
mentioning
confidence: 99%
“…Eq. (46) is valid in the time scale in which we neglect internal relaxation in the ground state subspace. This is possible since we have a separation of the time scales: the prefactor κ(E j ) in W (j,0 1 )→g and W (j,0 1 )→0 is ruled by the gap κ(E j ) κ(E gap ) and, at the same time, the overlap factor χ ± (j,0 1 ) involves a delocalized, extended state in the chain with one localized state at the end.…”
Section: Results For the Transverse Ising Modelmentioning
confidence: 99%